THE IMPLEMENTATION OF TECHNOLOGY READINESS AND ACCEPTANCE MODEL FOR INDUSTRIAL RESILIENCE IN BATIK MSME DURING THE DISRUPTION ERA - Siti Zulaikha Wulandari; Asmi Ayuning Hidayah; Fitri Amalinda Harahap; Indrawan Firdauzi (SEAN Institute, 2023)
This research aims to analyze the readiness and acceptance of Batik UKM technology and analyze the influence of perceived ease of use and perceived usefulness of technology on interest in using technology in Batik UKM. This research is survey research with a quantitative approach which aims to test hypotheses. The population in this study were Batik UKM owners spread across 20 batik center villages in Purbalingga. Determining the sample uses a purposive sampling technique, namely selecting a group of subjects based on certain considerations, with the aim of obtaining sampling units that have the desired characteristics so that 100 are obtained. The analytical method used in this research is SEM PLS. The results of research conducted by researchers show that perceived ease of use has a positive effect on perceived usefulness and perceived usefulness has a positive effect on intention of use. Meanwhile, perceived ease of use and technology readiness do not influence intention of use. We also found that technology readiness had a positive effect on perceived ease of use but had a negative effect on perceived usefulness.